COMPARATIVE ANALYSIS OF PHYSICS ASSESSMENT MATERIAL AND FORMS IN THE INDEPENDENT CURRICULUM FOR SENIOR HIGH SCHOOL AND CAMBRIDGE A LEVEL - Sari, Dinda Permata (Journal of Higher Education and Academic Advancement, 2025)
Objective: This study aims to conduct a comparative analysis of Physics materials and assessment formats between the Independent Curriculum Phase F (Indonesia) and the Cambridge International A-Level Physics (9702). Method: A qualitative content analysis was employed to examine curriculum documents and official guidelines from both educational systems. Results: The findings reveal that both curricula follow a similar structural framework consisting of planning, implementation, and evaluation stages. While the topics covered in both curricula show substantial overlap, distinctive features were identified. The Independent Curriculum emphasizes a contextualized learning approach rooted in local wisdom, whereas the Cambridge Curriculum prioritizes critical thinking and global competencies. A notable divergence lies in their assessment models: the Independent Curriculum incorporates authentic, project-based, and portfolio assessments, while the Cambridge Curriculum adopts paper-based examinations aligned with international standards. Novelty: This study offers a unique insight into how culturally contextual and globally standardized physics curricula can be contrasted and potentially integrated to foster an adaptive, high-quality learning experience that meets both national and international benchmarks.